Dynamic Simulation of a Multiproduct Chemical Plant - Lozada, Alejandro (My University, 1971)
This report deals with the use of the "Modular Approach", in the simulation of change-over operations, for a continuous multiproduct chemical plant. A dynamic model of the continuous fat hydrolysis process was built, with the DYNSYS framework, with the purpose of evaluating the usefulness of this programme in simulating different change-over operation policies. Operator's activities were simulated making use of an interactive version of DYNSYS, demonstrating its value for studying alternate changeover policies and possible as a training device. Supervisory control was implemented in order to automate the change-over operations, simulating the functions of a small computer controlling the process. Improved operating policies for change-over are proposed and the validity of the simulation is discussed from both a practical and a theoretical point of view.
Keywords: Modular Approach; change-over operation; chemical plant; fat hydrolysis process; DYNSYS